Alterações metabólicas se relacionam à doença periodontal - Paizan, Mara Lucia Macedo (2010)
Analyze the socio-demographic profile and the organization of health services as the primary gateway to the tuberculosis diagnosis. Methods: This is an exploratory descriptive study, conducted from a quantitative approach, with patients living in the city of Sao Jose do Rio Preto in 2009. A structured questionnaire that follows the reference of the Primary Care Assessment Tool for tuberculosis care was used, focusing on issues related to socio-demographic information and the gateway size. The data analysis was performed by means of frequency distribution and chi-square test for proportions and analysis of residuals. Results: The first health service sought after onset of symptoms was the Emergency Care, followed by Primary Health Care. Regarding the variables of gateway size there was a strong association between patients who sought the services closer to his home to the onset of signs and symptoms of tuberculosis and looked for the Primary Health Care and those who sought the services further away and went directly to the specialist services. Also was found between patients who were no preventive control of health and the search for Emergency Care. Conclusions: The main gateway to the respiratory symptoms is not Primary Health Care as recommended by the National Tuberculosis Control but the Emergency Care.